PENGUKURAN EFISIENSI EKONOMI USAHATANI JAGUNG NGGELA (JAWA NGGELA) DI KABUPATEN ENDE - Willybrordus Lanamana (AGRICA, 2017)
Economic Efficiency Measurement of Nggela Corn Farming (Jawa Nggela) at Ende Regency. This research aimed to: (1) analyze the economic efficiency level of Nggela corn farming and (2) analyze the factors which have an impact on economic efficiency. Data analysis use a production function approach and stochastic frontier cost function. The data analysis result shows that the seed price variable and fertilizer price give real effect at 99 % insignificance level, positive marked. Workers wage have no effect on production costs and negative marked. Production variables give a real effect at 99 % significance level. The average of Nggela corn farmers economic efficiency level is in the high category. The factors which have an effect on the economic efficiency of Nggela corn farming are; farmers age, duration of farming, frequency of getting information, members of farmer groups and the other income sources.